2018
DOI: 10.1177/0009922818769405
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Substance Use Associations With E-Cigarette Use in US Adolescents

Abstract: Concerns exist that e-cigarette use may introduce adolescents to drugs. This study explores trends and associations of inhaled tobacco use with drug use. We performed a secondary data analysis on the National Youth Risk Behavior Survey examining the inhaled tobacco and drug use patterns among US teens. Adjusted odds ratios were calculated using bivariate and multivariate analyses between inhaled tobacco use with other drug use, adjusting for age, race/ethnicity, and gender. When adjusting for gender, age, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…Of 835 potentially relevant studies identified through the database search and 4 through the gray-literature search, 158 reports appeared potentially eligible after title and abstract screening. After exclusion of 137 studies through full-text screening, including 3 studies with overlapping data sets, [28][29][30] 21 studies were found to be eligible [5][6][7]23,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and were included in the qualitative and quantitative syntheses. All studies were observational; there were 3 longitudinal studies 6,7,45 representing 14 364 participants and 18 cross-sectional studies 5,23,[31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47 representing 113 863 participants in total.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 835 potentially relevant studies identified through the database search and 4 through the gray-literature search, 158 reports appeared potentially eligible after title and abstract screening. After exclusion of 137 studies through full-text screening, including 3 studies with overlapping data sets, [28][29][30] 21 studies were found to be eligible [5][6][7]23,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and were included in the qualitative and quantitative syntheses. All studies were observational; there were 3 longitudinal studies 6,7,45 representing 14 364 participants and 18 cross-sectional studies 5,23,[31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47 representing 113 863 participants in total.…”
Section: Resultsmentioning
confidence: 99%
“…Pooling of data from all studies ( Figure 1) suggested that ENDS use is associated with an increased risk of marijuana use (AOR, 3.47 [95% CI, 2.63-4.59]; I 2 , 94%). Subgroup analysis by study type ( Figure 2) revealed significantly increased odds of marijuana use in both longitudinal (3 studies 6,7,45 ; AOR, 2.43 [95% CI, 1.51-3.90]; I 2 , 73.8%) and cross-sectional studies (18 studies 5,23,[31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47 ; AOR, 3.70 [95% CI, 2.76-4.96]; I 2 , 94%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Hawaiian adolescents, dual users had higher risk of experiencing difficulties with academics and behavioral regulation [53]. Moreover, dual users among US teens were more likely to have ever drunk alcohol, currently drink alcohol, have ever tried marijuana, currently use marijuana, and have used drugs in their lifetime [54]. This suggests the need for continued tobacco regulatory efforts toward adolescents, including multiple forms of tobacco use, with strict regulation of new and emerging products.…”
Section: Discussionmentioning
confidence: 99%
“… 23 - 27 In addition, young current vape users often have friends and family members who vape or who accept vaping, 28 and use other substances including cigarettes and marijuana. 29 - 31 …”
Section: Introductionmentioning
confidence: 99%